2019
DOI: 10.1073/pnas.1900401116
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst activation engenders transcriptome reprogram affecting X-chromosome reactivation and inflammatory trigger of implantation

Abstract: Implantation of the blastocyst into the uterus is the gateway for further embryonic development in mammals. Programming of blastocyst to an implantation-competent state known as blastocyst activation is the determining factor for implantation into the receptive uterus. However, it remains largely unclear how the blastocyst is globally programmed for implantation. Employing a delayed implantation mouse model, we show here that the blastocyst undergoes extensive programming essential for implantation. By analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 47 publications
5
52
2
Order By: Relevance
“…Importantly, we propose that the dynamics of the paused stage, embryonic diapause are affected by microRNA regulated stress and inflammation response genes. This is interesting in the light of recent publications that have revealed importance of stress response and inflammation in regulation of embryonic diapause and stem cell quiescence [35,88,89], and calls for further analysis on microRNA contribution in stress induced regulation of pause in development.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, we propose that the dynamics of the paused stage, embryonic diapause are affected by microRNA regulated stress and inflammation response genes. This is interesting in the light of recent publications that have revealed importance of stress response and inflammation in regulation of embryonic diapause and stem cell quiescence [35,88,89], and calls for further analysis on microRNA contribution in stress induced regulation of pause in development.…”
Section: Discussionmentioning
confidence: 98%
“…Diapaused embryos can resume their normal development in response to favorable environments ( He et al., 2019 ; Renfree and Fenelon, 2017 ). To determine whether quiescent ESCs are capable of responding to distinct environmental cues, we analyze their behaviors under self-renewal and differentiation conditions.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…In each well of a 96-well plate, 1x10 4 Ishikawa cells were cultured as attached monolayers overnight. Then different dosage of TNF-α (R&D, Minneapolis, MN, USA) and ETA were used to treat the cell line.…”
Section: Cell Counting Kit-8 Analysismentioning
confidence: 99%
“…Using mice embryo activation model, Wang et al has found that several cytokines, including TNF-α, is activated when embryo form dominancy to the activated status and play roles in Xchromosome reactivation. 4 Therefore, dysregulation of these factors would potentially cause the skewed cross-talk of embryo and endometrium, which could lead to implantation failure in clinic.…”
Section: Introductionmentioning
confidence: 99%